PENGARUH GAYA KEPEMIMPINAN, BUDAYA ORGANISASI DAN MOTIVASI, TERHADAP KEPUASAN KERJA. Studi Di Lembaga Pendidikan Dan Kebudayaan Indonesia Korean Culture Study - Nina Imaniar; Ahmad Faisal (Jurnal Ilmiah Manajemen SURYA PASCA SCIENTIA, 2022)
The purpose of this research is to study comprehensively the effect of leadership style, organizational, and motivation on job satisfaction. The research was conducted the sample used was 90 people with 20 respondents to test the research instrument. The sample selection used in this study is simple random sampling. Hypothesis testing is done empirically using Path Analysis using the SPSS Version 24 program. The research showed that Leadership Style (X1), Organizational Culture (X2) affect Motivation (X3) and as far as where is Leadership Style (X1), Organizational Culture (X2), and Motivation (X3) influencing Job Satisfaction (Y). The results showed that leadership style (X1) had a direct effect on Motivation (X3) of = 0,570 or 57,0%, Organizational Culture (X2) had a direct effect on Motivation (X3) of = 0,256 or 25,6%, leadership style (X1) direct effect on Job Satisfaction (Y) of = 0,231 or 23,1%, Organizational Culture (X2) direct effect on Job Satisfaction (Y) of = 0,458 or 45,8%, Motivation (X3) direct effect on Job Satisfaction (Y) of = 0,205 or 20,5%. Therefore Leadership Style is the most dominant variable that can improve Motivation. Organizational culture is the most variable that can improve the Job Satisfaction of employees in Indonesia Korean Culture and Study. Keywords: Leadership Style, Organizational Culture, Motivation, Job Satisfaction.